Book Review – Studies on Islam and Society in Southeast Asia - Riddell, Peter (Penerbit Universiti Sains Malaysia (USM Press), 2011)
This work provides a valuable window into the prolific scholarly output by William Roff during his long (and continuing) academic career. Readers are urged to take the time to read the Introduction, which provides the author's overview of his own career and his evolving scholarly context. It reveals how he was almost lost to Malay Studies because of his early interest in Burma and Buddhism. Roff unpacks for the reader the changing preoccupations and trends in the study of Islam in Southeast Asia and, as such, this short introduction is itself a valuable resource for young students of Southeast Asian studies. Roff's career has been characterised by both longevity and breadth. He has spent over forty years of his life researching the modern history of Islam and Muslims, with particular reference to Southeast Asia and its social and intellectual history. The fifteen essays contained in this present volume were originally published between 1964 and 2009. They cover wide-ranging themes, though the connections across the themes are clear and provide a powerful coherence to the volume.